(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
The larger grain borer (Prostephanus truncatus Horn) is a destructive storage pest of dried cassava chips in sub-Saharan Africa. This study evaluated the effects of cassava processing methods and a botanical insecticide on adult mortality and postharvest damage of dried cassava chips. Chips were processed using two methods, parboiling and non-parboiling (plain)—and treated with graded concentrations of Zingiber officinale extract (500, 250, 125, and 62.5 µL/mL), alongside a reference insecticide and an untreated control. One hundred grams of each processed and treated sample were infested with ten unsexed adult P. truncatus under laboratory conditions. Adult mortality was recorded at 24, 48, and 72 h, and 7 days after treatment, while weight loss, perforation, and adult emergence were assessed following a 14-day oviposition period and an additional 25-day observation period. Data were analyzed using analysis of variance (ANOVA), and treatment means were separated using least significant difference (LSD) at P < 0.05. Results showed that both processing method and Z. officinale concentration significantly influenced adult mortality and damage parameters (P < 0.05). At 500 µL/mL, adult mortality reached 100% at 7 DAT, while lower concentration (62.5 µL/mL) resulted in 68–70% mortality. Weight loss and perforation were completely prevented (0.00%) at 250–500 µL/mL, compared to the untreated control (86.33% weight loss and 100% perforation). Parboiled chips showed lower damage at moderate concentration, with reduced weight loss (4.67% vs 10.33%) and perforation (10.00% vs 15.66%) at 125 µL/mL. The findings indicate that combining parboiling with Z. officinale extract is an effective, low-cost postharvest strategy for reducing P. truncatus infestation and preserving the quality of dried cassava chips.